Using Wii™-assisted motivational interviewing to increase therapeutic engagement and therapeutic alliance with at-risk adolescents - McGrath, Randall T., Jr., author; Zimmerman, Toni, advisor; Haddock, Shelley, advisor; Browning, Ray, committee member (Colorado State University. Libraries, 2012)
Adolescents are a difficult population to form an alliance with and engage in psychotherapy, especially when they do not enter into a therapeutic relationship voluntarily. The present study sought to answer the question of whether using the Nintendo Wii™ videogame console with motivational interviewing therapy will increase therapeutic alliance and therapeutic engagement with adolescent clients more than when using motivational interviewing techniques alone. Justification for focusing on the constructs of therapeutic alliance and therapeutic engagement, and the use of motivational interviewing therapy is presented. An examination of the use of videogames in psychotherapy is also included. Results indicated that no differences exist with regard to therapeutic alliance or therapeutic engagement between treatment groups for the given sample, but support was shown for the theoretical view that engagement (both on the part of the client and the therapist) and alliance are linked constructs. A discussion of the limitations for this study and suggestions for future directions are provided.